Obesity/Overweight and the Role of Working Conditions: A Qualitative, Participatory Investigation. Issue 1 (January 2016) - Nobrega, Suzanne; Champagne, Nicole; Abreu, Marlene; Goldstein-Gelb, Marcy; Montano, Mirna; Lopez, Isabel; Arevalo, Jonny; Bruce, Suezanne; Punnett, Laura
The rising U.S. prevalence of obesity has generated significant concern and demonstrates striking socioeconomic and racial/ethnic disparities. Most interventions target individual behaviors, sometimes in combination with improving the physical environment in the community but rarely involving modifications of the work environment. With 3.6 million workers earning at or below the federal minimum wage, it is imperative to understand the impact of working conditions on health and weight for lower income workers. To investigate this question, a university–community partnership created a participatory research team and conducted eight focus groups, in English and Spanish, with people holding low-wage jobs in various industries. Analysis of transcripts identified four themes: physically demanding work (illnesses, injuries, leisure-time physical activity), psychosocial work stressors (high demands, low control, low social support, poor treatment), food environment at work (available food choices, kitchen equipment), and time pressure (scheduling, having multiple jobs and responsibilities). Physical and psychosocial features of work were identified as important antecedents for overweight. In particular, nontraditional work shifts and inflexible schedules limited participants' ability to adhere to public health recommendations for diet and physical activity. Workplace programs to address obesity in low-wage workers must include the effect of working conditions as a fundamental starting point.